Analisis Kualitas Palm Kernel Oil pada PT. Ujong Neubok Dalam Menggunakan Metode Statistical Quality Control - Kasmawati, Kasmawati; Alfarishi, M.; Sofiyanurriyanti, Sofiyanurriyanti (Jurnal Optimalisasi, 2024)
PT. Ujong Neubok Dalam is a company engaged in the plantation and processing of fresh fruit bunches (FFB) of oil palm which produces the main product, namely palm kernel oil (PKO). The quality of palm kernel oil is influenced by water, dirt, and free fatty acids. Production quality can be good if the established standards produce the product. To achieve the established product quality, companies often experience obstacles that can cause defects, thereby reducing product quality. The purpose of this study was to identify the level of defects and the causes of defects against the standards set by the company using the Statistical Quality Control (SQC) method and to describe improvement efforts. In using the SQC method, there are 5 tools used for quality control, namely check sheets, histograms, Pareto diagrams, control chart diagrams, and fishbone diagrams. Based on the results of data processing, the highest percentage of defects is the Free Fatty Acid content of 93%, Water content of 6%, and dirty content of 1%. The high number of defects is caused by work method factors, humans, machines, and materials. Improvement efforts that can be made are by providing training, supervision, routine machine maintenance, and preventing the accumulation of nuts in the factory.